Making environmental DNA (eDNA) biodiversity records globally accessible. Issue 4 (21st December 2020) - Berry, Oliver; Jarman, Simon; Bissett, Andrew; Hope, Michael; Paeper, Corinna; Bessey, Cindy; Schwartz, Michael K.; Hale, Josh; Bunce, Michael
Abstract: Environmental DNA (eDNA) metabarcoding, where specific DNA markers (barcodes) are purified from the environment, sequenced, and used to identify organisms, is revolutionizing biodiversity science. Researchers, industry, and governments are increasingly incorporating eDNA surveys into their toolkits for biomonitoring because of their high accuracy, taxonomically holistic lens, and ease of deployment. Yet, the full value of this rich and revolutionary technique is not being realized because eDNA data are rarely maintained in consistent formats or on open platforms that facilitate easy re‐use or integration with other data layers. Here, we discuss opportunities to improve the accessibility and "FAIRness" of eDNA records with the aim to maximize the value of this remarkable source of information on environmental state and change. Abstract : Environmental DNA (eDNA) is a new and sensitive approach for detecting organisms and making biodiversity assessments that is transforming environmental science and biomonitoring. The value of eDNA data could be boosted significantly if incorporated into user‐friendly open spatial biodiversity portals alongside conventional biodiversity and environmental records. We outline principles for the management and serving of eDNA records so that the global community can take full advantage of this rich source of information on environmental condition and change.